Interspecific interactions involving Neoseiulus californicus (Acari: Phytoseiidae) and Agistemus brasiliensis (Acari: Stigmaeidae) as predators of Brevipalpus phoenicis (Acari: Tenuipalpidae) - Silva, Marcos Zatti da; Sato, Mario Eidi; Leite de Oliveira, Carlos Amadeu [UNESP]; Nicastro, Roberto Lomba (Springer, 2015)
Brevipalpus phoenicis (Geijskes) is associated with the transmission of Citrus leprosis which is considered the main viral disease for the Brazilian citrus production. Mites of the families Stigmaeidae and Phytoseiidae coexist in various agricultural crops, often promoting the biological control of pest mites. The aim of this work was to study the interactions of Neoseiulus californicus (McGregor) (Phytoseiidae) and Agistemus brasiliensis Matioli, Ueckermann &Oliveira (Stigmaeidae), in the presence or absence of B. phoenicis. Two experiments were carried out. In the first, a N. californicus female was placed in each leaf disc arena, with eggs of B. phoenicis and A. brasiliensis as food sources. In the second, an A. brasiliensis female was placed in each arena, with eggs of B. phoenicis and N. californicus as food sources. Adults of both predators were able to consume both types of eggs available as food sources, but they fed on considerably higher proportions of B. phoenicis than on eggs of the predator. Eggs of A. brasiliensis were not a suitable food source for N. californicus, which produced only 0.1 egg per female per day when only eggs of that species were present in the experimental unit. The results suggest that eggs of N. californicus were a suitable food source for A. brasiliensis, which oviposited 1.12 eggs per day, when only eggs of N. californicus were provided to the stigmaeid mite. The possible interactions among N. californicus, A. brasiliensis and B. phoenicis in citrus orchards are discussed.
Keywords: Predaceous mites; Phytophagous mites; Interspecific competition; Biological control